Pengaruh Teknik Modeling Simbolis Biografi Tokoh Karier Terhadap Pengambilan Keputusan Karier Siswa - Cipta, Aswidy Wijaya; Ibrahim, Muhammad; Sinring, Abdullah (JURKAM: Jurnal Konseling Andi Matappa, 2018)
Objectives: (1)find out description of the career decision-making students of class XI IPA before and after given knowledge of career decision making through symbolic modeling techniques using biographies, (2)knowing influence of symbolic modeling techniques using biographies against career decision-making of IX IPA students. This is quantitative experimental research with Pretest-Posttest Control Group Design. Data collected using instrument of observation and question form. Data analyzed by descriptive and t-Test. Results: (1)description of the influence of symbolic modeling techniques using biographies career that used in student's career decision making through 4 step, namely: giving information about career decision making, giving information about symbolic modeling and biographies, granting preferential treatment in biographies about career, and follows activities of the group inverse. Before being given symbolic modeling techniques both of experimental group or control group generally are at low category. After being given treatment shows the changes of the level of decision making career choices from low to high, while the categories for students who were not given the treatment showed no change or remain in the middle category. (2) there is  significant issue about symbolic modeling techniques using biographies, in case to increased career decision-making student at SMA Negeri 9 Makassar.